2017
DOI: 10.1080/20426445.2016.1275093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of knots on the fracture propagating along grain in timber beams

Abstract: Fracture propagating along the grain of timber is one of the most relevant failure mechanisms due to the wood's low strength and its brittle failure behaviour when subjected to excessive shear and tensile stresses perpendicular to the grain. According to the current procedures, the fracture energy of wood is determined on small clear specimens. However, for the prediction of the structural behaviour of full-scale structural timber members, the influence of knots has to be accounted for. The discrepancy between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…PRG320 is the only one of these three standards that restricts the inclusion of knots over and above structural grading requirements. Given that knots show good potential for central layers because of their good rolling [23] and longitudinal shear [21,22] performance, it would be beneficial to utilize them in CLT. But given their negative impact on bond performance, it would be unwise not to restrict their inclusion, as they could reach a level that is detrimental to the bond performance of the panel.…”
Section: Maximizing Out-of-grade Into Cltmentioning
confidence: 99%
See 1 more Smart Citation
“…PRG320 is the only one of these three standards that restricts the inclusion of knots over and above structural grading requirements. Given that knots show good potential for central layers because of their good rolling [23] and longitudinal shear [21,22] performance, it would be beneficial to utilize them in CLT. But given their negative impact on bond performance, it would be unwise not to restrict their inclusion, as they could reach a level that is detrimental to the bond performance of the panel.…”
Section: Maximizing Out-of-grade Into Cltmentioning
confidence: 99%
“…In fact, the majority of publications focus on the bonding of mature rather than juvenile wood [20]. Moreover, researchers intentionally excluded large knots from their studies [18,20] even though knots have shown good shear performance [21][22][23][24], which is desirable for inner layers in glue-laminated timber (Glulam) and CLT.…”
Section: Introductionmentioning
confidence: 99%
“…Developing timber structure buildings is conducive to achieving the national goals of peaking carbon emissions and carbon neutrality. timber columns are the main compressive components in timber structure buildings, but natural defects in wood, such as knots and cracks, limit their application in timber column components [2]. Therefore, reasonable and effective reinforcement methods are crucial for timber column components.…”
Section: Introductionmentioning
confidence: 99%
“…The assumptions for the analysis were taken from the theory of laminar flow around a still obstacle [ 10 , 20 ]. In one model, steeped elliptic obstacles reflected knots, and the fluid flow path represented fiber deflection [ 21 , 22 , 23 , 24 ]. Another model involving flow-grain analogy was suggested by Guindos [ 25 ].…”
Section: Introductionmentioning
confidence: 99%